(untitled) (Journal of the College of Languages (JCL), 2021)
Reading and analyzing Paula Vogel’s plays, the readers can attest that she achieves success in drama or theater because she is passionate about theater. Vogel is a modern American playwright who won the 1998 Pulitzer Prize for drama. Her success and insight in playwriting or in adapting do not come all of a sudden; she is influenced by many writers. Vogel is influenced by many American dramatists, including Eugene O’ Neill, Arthur Miller, Tennessee Williams, and Edward Albee, and by other non-American writers, including August Strindberg, Anton Chekhove, and Bertolt Brecht. Certainly, there were female playwrights who wrote preeminent plays and they influence Vogel as well. Nevertheless, dramas by female writers, as a matter of fact, remain marginalized. This paper focuses on the influence of some female playwrights on Vogel.